2021
DOI: 10.1182/blood-2021-146178
|View full text |Cite
|
Sign up to set email alerts
|

Pozelimab, a Human Monoclonal Antibody Against Complement Factor C5, Provided Inhibition of Intravascular Hemolysis in Patients with Paroxysmal Nocturnal Hemoglobinuria

Abstract: INTRODUCTION Paroxysmal Nocturnal hemoglobuinuria (PNH) is a rare, acquired, life-threatening disorder characterised by intravascular hemolysis and increased risk of thrombosis. Current available treatments represent a significant burden to patients and include anti-complement factor 5 (C5) therapies, eculizumab and ravulizumab, both intravenous infusions, or more recently, twice weekly C3 inhibitor, Pegcetacoplan, a subcutaneous (SC) infusion treatment. Pozelimab (REGN3918), a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study examines a combination therapy of the mAb with Cemdisiran, an N-acetylgalactosamine (GalNAc) conjugated RNA interference (RNAi) therapeutic. This C5 inhibitor has been evaluated for paroxysmal nocturnal hemoglobinuria (PNH), CD55-deficient protein-losing enteropathy, and CHAPLE disease [ 37 , 38 ]. Other C5 inhibitors designed and studied for other diseases may, in the future, be studied for possible therapeutic effects in MG patients.…”
Section: Resultsmentioning
confidence: 99%
“…This study examines a combination therapy of the mAb with Cemdisiran, an N-acetylgalactosamine (GalNAc) conjugated RNA interference (RNAi) therapeutic. This C5 inhibitor has been evaluated for paroxysmal nocturnal hemoglobinuria (PNH), CD55-deficient protein-losing enteropathy, and CHAPLE disease [ 37 , 38 ]. Other C5 inhibitors designed and studied for other diseases may, in the future, be studied for possible therapeutic effects in MG patients.…”
Section: Resultsmentioning
confidence: 99%
“…The initial dose is administered intravenously, followed by weekly subcutaneous injections. Clinical evidence has demonstrated that pozelimab administration effectively inhibits intravascular hemolysis and is generally well-tolerated (Jang et al 2021 ). Common AE to the therapy include upper respiratory tract infections, fractures, urticaria, and alopecia.…”
Section: Genetic Disordersmentioning
confidence: 99%
“…This study examines a combination therapy of the mAb with Cemdisiran, an Nacetylgalactosamine (GalNAc) conjugated RNA interference (RNAi) therapeutic. This C5 inhibitor has been evaluated for paroxysmal nocturnal hemoglobinuria (PNH), CD55-deficient protein-losing enteropathy and CHAPLE disease [37,38]. Other C5 inhibitors designed and studied for other diseases, may in the future be studied for possible therapeutic effects in MG patients.…”
Section: Monoclonal Antibodies For Complement Inhibitionmentioning
confidence: 99%